Relación de la concentración de proteínas totales y albúmina sérica en adultos según edad y sexo, pertenecientes al sector Las Lomas de Huanchaco, Julio - 2014 - Quiroz Rodríguez, Diego Armando (2017)
The present research work was carried out in Las Lomas de Huanchaco sector, in July 2014, with the objective of determining the relationship of total protein concentration and serum albumin in adult volunteers according to age and sex. Processing a total of 87 blood serum samples of adults of both sexes, using the colorimetric method of Wiener. A survey was conducted to collect information on personal data, nutritional aspects, socioeconomic level and lifestyle, allowing us to interpret the results obtained. Concluding that there is no statistical significance between the correlation of total proteins with sex (p = 0.534) and age (p = 0.611), there is no statistical significance between serum albumin correlation with sex (p = 0.226) and age (P = 0.353).